National Strategies And Continent-Wide Facilitation For The Implementation Of Open Science Practices In Africa - Mchunu, Nokuthula P. (My University, 2023)
Presentation held at NISO.plus 2023: African Open Science Platform (AOSP) - Vision and Strands “African scientists are at the cutting edge of contemporary, data-intensive science as a fundamental resource for a modern society. They are innovative global exponents and advocates of Open Science and leaders in addressing African and Global Challenges.”
Keywords: National Strategies; Open Science; African scientists